Non-invasive fluorescence sensing reveals changes in intestinal barrier function and gastric emptying rate in a first-in-human study of Crohn’s disease - Jonathan Gan; Qian Chen; Elena Monfort Sanchez; Nilanjan Mandal; Jiacheng Xu; Zixin Wang; Arjun Agarwal; Emmanuel Oluwatunmise; Pratik Ramkumar; Ash Salam; Elena Chekmeneva; María Gómez-Romero; et al. (Therapeutic Advances in Gastroenterology)
Background: Crohn’s disease is characterised by multifaceted changes in gut function, involving not just inflammatory effects but also alterations in gut barrier function and gastric motility. However, current diagnostic tools used to measure key gut functional parameters are invasive, unreliable or time-consuming. Thus, we applied a novel, non-invasive fluorescence sensing technology – transcutaneous fluorescence spectroscopy (TFS) – to investigate gut barrier function and gastric emptying in Crohn’s disease. Objectives: Our study aimed to validate TFS for non-invasive gastrointestinal (GI) diagnostics and to explore changes in gut barrier function and gastric emptying rate simultaneously in Crohn’s disease. Design: A cross-sectional study involving patients with Crohn’s disease and healthy individuals. Methods: We performed fluorescent measurements and lactulose:mannitol (L:M) tests in 38 Crohn’s disease patients and 20 healthy volunteers. We investigated multiple TFS-derived parameters as indicators of gut barrier function and gastric emptying rate. Using these parameters, we assessed differences between healthy volunteers, inactive Crohn’s patients and active Crohn’s patients, and calculated correlations between TFS and L:M values. Results: TFS-derived parameters revealed significantly increased intestinal permeability and delayed gastric emptying in patients with active Crohn’s compared to healthy controls. TFS trends showed encouraging alignment with those from the L:M test, suggesting potential concordance with established methods. No adverse events were reported. Conclusion: TFS enables rapid, non-invasive discrimination of Crohn’s patients from healthy volunteers and allows simultaneous assessment of gut barrier function and gastric emptying rate – two important aspects of GI function in Crohn’s disease. This implies potential for improved monitoring and diagnosis of Crohn’s disease (and other gut disorders) as well as more advanced study of gut function in health and disease. Trial registration: The clinical study reported in this article was registered with ClinicalTrials.gov prior to enrolment of the first participant. https://clinicaltrials.gov/study/NCT03434639 and Registration number: NCT03434639.